URGENSI LINGKUNGAN HIDUP DALAM ISLAM - Eni Murdiati (Wardah, 2013)
Islam as a religion that not only regulates man's relationship with God, but also relationships with fellow human beings (including the environment), actually has a normative basis either implicitly or explicitly on the management of the environment. Harmonisation of environmental and human subsistence is derived from natural resources should be a serious concern to keep and maintain a balance of human and other beings of divine creation.